2021
DOI: 10.1097/cji.0000000000000356
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Troponin I and T in Checkpoint Inhibitor–associated Myositis and Myocarditis

Abstract: Checkpoint inhibitor-associated myocarditis (ir-myocarditis) and myositis (ir-myositis) may occur concurrently among patients on checkpoint inhibitor immunotherapy. While cardiac-specific troponin I (cTnI) and troponin T (cTnT) are regarded to have similar sensitivities and specificities in conditions such as acute coronary syndrome, the cardiac specificity of cTnT has been challenged following observation that patients with neuromuscular diseases, including myositis, may have elevated cTnT without apparent cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Eleven cases had cardiac magnetic resonance imaging (MRI) with features suggestive of myocarditis [4, 14, 20, 29–33]. Although a full description of MRI findings was not available in all cases, Arora et al described evidence of myocardial edema and late gadolinium enhancement in the subepicardial midinferior wall consistent with acute myocarditis in one case.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven cases had cardiac magnetic resonance imaging (MRI) with features suggestive of myocarditis [4, 14, 20, 29–33]. Although a full description of MRI findings was not available in all cases, Arora et al described evidence of myocardial edema and late gadolinium enhancement in the subepicardial midinferior wall consistent with acute myocarditis in one case.…”
Section: Resultsmentioning
confidence: 99%
“…One case reported negative inflammatory cell infiltration or necrosis [24]. Fifteen cases had cardiac biopsies [10, 12, 13, 18, 22, 24, 31, 33–36, 39, 40]. Most cases described lymphocytic infiltrate (which was positive for T‐cell markers, both CD4 and CD8) with CD68 positive macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…At presentation, most patients present with an abnormal electrocardiogram (ECG) and cardiovascular symptoms, usually with elevated troponin, creatinine kinase MB or/and B-type natriuretic peptide (BNP)/N-terminal prohormone of BNP (NT-pro BNP) levels. It has been discussed, whether troponin T remains a good biochemical marker of myocarditis, as it is found in fetal skeletal muscle and it might be less cardiac-specific than troponin I in the presence of neuromuscular pathologies such as ICI-associated myositis [ 51 ]. In one study, it was observed that 94% of patients with ICI-related myocarditis ( n = 35) had an increased troponin level [ 12 ].…”
Section: Review and Discussionmentioning
confidence: 99%
“…It is important to check both CK and aldolase in patients with symptoms concerning for ICI myositis. Another marker that is expressed in regenerating skeletal muscle cells is cardiac troponin T, which can also be elevated in ICI myositis 25 . However, another type of cardiac troponin, cardiac troponin I, is not present in healthy adult skeletal muscle cells and is more specific for cardiac muscle tissue; thus, it can be used in the workup of suspected concomitant myocarditis 18,25 .…”
Section: Laboratory Markersmentioning
confidence: 99%
“…Another marker that is expressed in regenerating skeletal muscle cells is cardiac troponin T, which can also be elevated in ICI myositis. 25 However, another type of cardiac troponin, cardiac troponin I, is not present in healthy adult skeletal muscle cells and is more specific for cardiac muscle tissue; thus, it can be used in the workup of suspected concomitant myocarditis. 18,25 Liver enzymes, aspartate and alanine aminotransferases, are also present in skeletal muscle cells; therefore, elevations in aspartate aminotransferase and alanine aminotransferase may indicate ICI myositis and can be confused with ICI hepatitis.…”
Section: Laboratory Markersmentioning
confidence: 99%